Effects of Some Ameliorant on Chlorophyll a, Chlorophyll b and Total Chlorophyll on Sweet Corn Growth with Raised-Bed Soil Materials - Ronny Mulyawan; Akhmad Rizali Saidy; Rahmi Zulhidiani (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2020)
The raised-bed soil is a land management technology in South Kalimantan. Adding Ameliorant to the raised-bed soil as an effort to increase the utilization of support for the cultivation land. Chlorophyll or leaf green substances found in all green plants that carry out photosynthesis. Ameliorant applications can increase the chlorophyll content of plants to optimize plant growth. This study aims to look at the effect of giving several types of ameliorant to the content of chlorophyll (chlorophyll-a, chlorophyll-b and total chlorophyll) and the growth of corn planted on raised-bed soil. This research is an experiment in the laboratory and a greenhouse. This research was conducted using a Completely Randomized Design (CRD) Single Factor with the treatment tested was the type of ameliorant soil without treatment (control - K), soil + agricultural lime (dolomite - C), soil + palm empty fruit bunch ash (S), soil + rice husk ash (P) and soil + coal ash (B). All treatments were repeated 5 (five) replications so that there would be 25 units of the experiment. The results showed that the application of ameliorant in raised-bed soil using dolomite and oil palm empty fruit bunches ash with a dose of 5 tons ha-1 affected the content of chlorophyll-a and total chlorophyll in the growth of corn planted in raised-bed soil materials.